PEMBELAJARAN DI SEKOLAH SEBAGAI WAHANA PENGEMBANGAN KARAKTER PERSERTA DIDIK - Santoso, Handoko (LPPM UM Metro, 2016)
The character is always up to date to be discussed and it is necessary to continue to be discussed in order to develop the character of the students in particular and the nation in general. Low of character of learners will result in low quality of the nation in the future, otherwise the strength of character of the learners are expected to affect the progress of the nation and the state. Up to now there are many phenomena of lawlessness, including criminal events that do learners caused low character. Character development must get the attention of all parties, especially the world of education. A person's character is not permanent, the characters can be changed and developed. Education is becoming a tools for the right to develop the character of students. Each subject in the school should be used as a media to develop the character in addition to developing intellectual. For this purpose, an educator is required to have the ability to carry out learning that is able to develop the character of their students through the subject matter, also through the example of daily life, especially at school.